Geographic regulation of next generation broadband networks: A review of practical cases and recent literature - Roberto E. Balmer (International Telecommunications Society (ITS), 2015)
Alternative telecommunications operators have continuously invested in their own infrastructure in recent years. After more than a decade since liberalization, competitive conditions have substantially changed, especially in urban areas. European regulatory authorities have acknowledged this development by starting regional deregulation. Additionally, different forms of cooperative investments in next generation broadband have appeared on the market. This article reviews the theoretical and empirical literature on geographic regulation as well as practical cases. Based on this review it is suggested that regulators consider geographically segmented access prices to set optimal incentives for the investment in next generation broadband infrastructure.
Keywords: 330; next generation access; co-investment; geographic regulation